2003
DOI: 10.1074/jbc.m302259200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Varicella Zoster Virus IE62 Major Transactivator and Cellular Transcription Factor Sp1

Abstract: The varicella zoster virus (VZV) IE62 protein is involved in the activation of expression of all three kinetic classes of VZV proteins. Analysis of the viral promoter for VZV glycoprotein I has shown that the cellular factor Sp1 is involved in or required for the observed IE62 mediated activation. Co-immunoprecipitation experiments show that the two proteins are present in a complex in VZV-infected cells. Protein affinity pull-down assays using recombinant proteins showed that IE62 and Sp1 interact in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 63 publications
(58 reference statements)
6
85
0
Order By: Relevance
“…7, HCF-1 was not required for the recruitment of the RNAPII basal factor complex, which depended on the presence of the viral IE62 activator in concert with the ubiquitous cellular activator Sp1. The ability of IE62 to mediate the formation of this complex is consistent with in vitro studies indicating that IE62 interacts directly with TBP and TFIIB (26) and enhances the binding of TBP/TFIID (29). Additionally, the requirement for Sp1 for stable IE62 promoter occupancy underscores the importance of factors such as Sp1, which has been observed in studies of IE62-mediated activation (30).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…7, HCF-1 was not required for the recruitment of the RNAPII basal factor complex, which depended on the presence of the viral IE62 activator in concert with the ubiquitous cellular activator Sp1. The ability of IE62 to mediate the formation of this complex is consistent with in vitro studies indicating that IE62 interacts directly with TBP and TFIIB (26) and enhances the binding of TBP/TFIID (29). Additionally, the requirement for Sp1 for stable IE62 promoter occupancy underscores the importance of factors such as Sp1, which has been observed in studies of IE62-mediated activation (30).…”
Section: Discussionsupporting
confidence: 81%
“…In particular, stimulation of Sp1 occupancy in the presence of IE62 underscores the cooperative DNA binding suggested previously (SI Fig. 8) (29).…”
Section: Ie62-mediated Assembly Of the Basal Transcription Complex Ismentioning
confidence: 60%
See 1 more Smart Citation
“…Downregulation of the expression of AP-1 affects the efficiency of transactivation and effectiveness of replication . Similar reports underlining the importance of specific cellular components for herpesviral gene regulation have described the physical interaction of VZV IE62 with Sp1 or USF (Peng et al, 2003; and Patel et al (1998) showed that blocking HSVmediated translocation of NF-kB into the nucleus reduced virus yields by 90 %.…”
Section: Discussionmentioning
confidence: 61%
“…The requirement for HCF-1 in ORF10 induction of the VZV IE62 gene is consistent with in vitro studies that previously demonstrated VZV enhancer core complex assembly with Oct-1/ORF10/HCF-1 (31). However, VZV IE expression is also positively autoregulated by IE62, presumably via increasing the affinity of the TATA-binding protein (TBP) for the nonconsensus IE62 TATA element (40,41). Induction of the minimal VZV IE promoter by IE62 in an HCF-1-dependent manner suggests that HCF-1 may cooperatively facilitate this activity.…”
Section: Discussionmentioning
confidence: 99%